”Min storesøster går jo deroppe, så …”: Unges orienteringer mod ældre søskende i uddannelsesvalget - Højbjerg, Lea Høxbroe; Enemark, Nanna Ramsing (Tidsskrift for Professionsstudier, 2025)
This article examines how young people orient themselves towards their older siblings’ educational choices to inform and qualify their own considerations regarding upper secondary education. By doing so, the article nuances the understanding of young people’s educational choice-making. The study concentrates on the young people’s perspective and is based on longitudinal focus group interviews with pupils in grades 8 and 9 and the following school year. Drawing on Anthony Giddens’ concepts of identity and life planning in modernity, the analysis explores educational choice within the complexity young people face. The findings show that older siblings serve as a bridge and act as day-to-day relatable mediators of the unfamiliar education system and the young person. Through their insights and guidance, the system becomes more comprehensible, enabling reflections on aspirations, identity, and future pathways. Young people’s educational considerations and priorities are interwoven with their orientation towards their older siblings’ knowledge and advice. This helps answer ‘what-if’ questions and reduce the perceived complexity of the decision, thus influencing the young person’s life planning and identity development. Older siblings emerge as central actors in educational choice-making and as a source of knowledge that is central to acknowledge within the institutional praxis.